Pembangunan Berkelanjutan Desa : Strategi Mengatasi Kemiskinan dan Meningkatkan Kesejahteraan Masyarakat Desa Pasir Permit - Samin Lubis, Mara; Yulinda, Isma; Hayyah, Azka Wardatul; Nayatama, M. Adhwa (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2024)
Poverty alleviation is still the main target in sustainable development. From poverty alleviation efforts there are some problems that become problems in the implementation of alleviation and poverty resolution strategies in Pasir Permit Village which are carried out by the Village government, so that poverty alleviation is resolved properly. The implementation of this research uses Qualitative Descriptive observation. As well as the approach during the implementation in the form of field studies, research was carried out using direct observation in the field in the KKN Program conducted in Pasir Permit Village. The research methods used were interview, observation, field study and documentation. There are several strategies carried out by the Pasir Permit village government in poverty alleviation in Pasir Permit village, namely, distributing Direct Cash Assistance (BLT), assistance programs in the form of Food Security Assistance, Providing KIP Assistance (Smart Indonesia Card).